Shifting to virtual breastfeeding counseling for low-income women in the US during COVID-19: A partner-engaged multimethod evaluation of program adaptations - Rhodes, Elizabeth C.; Wilde LaPlant, Helen; Zahid, Mahrukh; Abuwala, Nafeesa; Damio, Grace; Crummett, Carrianne; Surprenant, Rebecca; Pérez-Escamilla, Rafael (Frontiers in Health Services, 2022)
Background: The Breastfeeding Heritage and Pride program (BHP) provides evidence-based breastfeeding peer counseling to low-income women. Due to the COVID-19 pandemic, BHP shifted from delivering in-person and virtual services to providing only virtual services. Program adaptations can impact implementation success, which could influence program effectiveness. We documented program adaptations and explored their impacts on implementation outcomes, guided by the Model for Adaptation Design and Impact. Methods: Through a community-clinical-academic partnership, we conducted in-depth interviews with 12 program implementers and peer counselors and conducted a rapid qualitative analysis. To efficiently capture information on adaptations over time, we collected and analyzed information from program meetings and extracted data from a program report. We then triangulated data from these multiple sources. Results: Peer counselors received training on virtual service delivery and increased supportive supervision. They recruited women via phone instead of in hospitals, which was viewed as feasible. In-person counseling visits at hospitals and clients’ homes were replaced with phone and video calls. Examples of changes to the content delivered included breastfeeding education in the context of the pandemic such as the latest COVID-related infant feeding guidance, provision of face masks, and more assistance with social and economic challenges. Although peer counselors increasingly adopted video calls as a substitute for in-person visits, they emphasized that in-person visits were better for relationship building, helping with breastfeeding problems like latching, and identifying barriers to breastfeeding in the home environment like limited familial support. While adaptations were reactive in that they were made in response to the unanticipated COVID-19 pandemic, most were made with clear goals and reasons such as to ensure the safety of peer counselors and clients while maintaining service delivery. Most adaptations were made through a systematic process based on program implementers’ expertise and best practices for peer counseling and were largely but not fully consistent with BHP’s core functions. Discussion: BHP was able to shift to virtual service delivery for continued provision of breastfeeding counseling during the pandemic. Overall, virtual services worked well but were less optimal for several aspects of counseling. Evaluations of program effectiveness of virtual services are still needed.